Organoleptic Testing Of The Use Of Purple Sweet Potato Flour On The Quality Of Cookies - mutiara, Dahlia; Gusnita, Wiwik; Holinesti, Rahmi; Andriani, Cici (Universitas Negeri Padang, 2024)
Cookies are dry cakes made from soft dough with a high fat content that are relatively crispy when broken and the cross-section of the pieces has a dense texture, made from a mixture of wheat flour, refined sugar, margarine, meizena flour and powdered milk. Purple sweet potatoes are more focused on developing flour and starch because the color of the flour produced is more like purple sweet potato flour, and purple sweet potatoes tend to be more fragrant and have a distinctive taste of purple sweet potatoes. So purple sweet potato flour can be used in making cookies. This research aims to analyze the effect of using 15%, 40% and 45% purple sweet potato flour on the quality of the shape, color, aroma, texture and taste of the cookies produced. This type of research is a pure experiment using a Completely Randomized Design method. The data used is primary data obtained directly from 3 expert panelists by filling in the organoleptic test format for the quality of cookies with the effect of using purple sweet potato flour. The data obtained was then tabulated in table form and Analysis of Variance (ANOVA) was carried out, if Fh>Ft then continued with the Duncan Test. The results of the research showed that there was a significant effect of using 15%, 40%, and 45% purple sweet potato flour on the quality of color (purple), aroma (fragrant purple sweet potato), and sweetness (sweet taste and distinctive taste of sweet potato). The best results from the cookie quality test using purple sweet potato flour were 45%.